CLIMATIC VARIABILITY AND CROP PRICE TRENDS IN WEST TENNESSEE: A BIVARIATE GRANGER CAUSALITY ANALYSIS - Rachna Tewari; Joey E. Mehlhorn; Scott D. Parrott; Jessica I. Hill (European Scientific Journal, ESJ, 2015)
Weather aberrations like drought and extremely high temperatures have been associated with adverse impacts on crop yields particularly in agricultural production areas that extensively rely on rainfall. Extremely dry weather accompanied with low or negligible precipitation often leads to crop failure, resulting in decline of supplies and increasing crop prices. Among the recent climatic events of importance, U.S agriculture as a whole experienced one of its worst droughts in mid-year 2012 over a three decade horizon. The 2012 drought had serious implications particularly in the major production areas of Midwest and Southeast U.S damaging vast portions of field crops like corn and soybeans subsequently leading to increase in farm prices. The objective of this study is to conduct a bivariate granger causality analysis for climatic indicators causing soybean price changes over a study period from 1975-2013. The results indicate that a significant causality was detected for precipitation impacting commodity price movements for soybeans. No significant evidence was obtained for the presence of Granger causality between temperature related indicators (maximum, minimum, and average) and soybeans prices. The outcome of this study provides an initial insight into the causality between climatic indicators and commodity price movements for soybeans in the study region, and emphasizes the existence of causality for commodity prices by precipitation changes as compared to changes in temperature, especially in the absence of irrigation based production in the region.